Efektivitas E-Modul pada Mata Pelajaran Dasar-Dasar Ketenagalistrikan Kelas X di Sekolah Menengah Kejuruan - Tio Martias; Hansi Effendi (Jurnal Pendidikan Teknik Elektro, 2023)
This research was conducted with the aim of analyzing the effectiveness of e-modules in the Basics of Electrical Engineering class X subject at SMK Negeri 1 West Sumatra. The method used is quantitative analysis. This research uses an experimental method in the form of a true experimental design. This research uses pretest and posttest question research instruments in objective form to see student learning outcomes and is tested using validity tests, reliability tests, differential power tests and question difficulty indexes to determine the feasibility of the instruments used. Based on the research results, it shows that the results of statistical analysis of the completeness of student learning outcomes and the average posttest score are 80.67 which is higher than the pretest average score of 72.4. Then, the results of the effect size analysis with a calculation result of 0.85. E-module media was effective in improving the learning outcomes of class X Electrical Power Installation Engineering (TITL) students in basic subjects. -basic electrical engineering at SMK Negeri 1 West Sumatra.